The Influence of Husband-Wife Interaction and Parent-Child Interaction on Family Subjective Well-Being in KB and Non-KB Villages - Suciyati Martinea; Euis Sunarti (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2019)
Family subjective well-being is an evaluation of satisfaction related to physical-economic, social, and psychological aspects. This study discussed husband-wife interactions, parent-child interactions, and family subjective well-being in Pasirjaya Village. This study used a cross-sectional design. This study involved 120 families who were selected by stratified random sampling by place of residence; Family planning participating village (KB village) and Family planning non-participating village (non-KB village) in KampungMuara, Pasirjaya Village, West Bogor. The results of the independent sample t-tests showed a higher average in KB village on husband-wife interactions (dimensions of love, directing, and respect) and parent-child interactions (dimension of directing). The results of the regression test showed a positive influence of the marriage duration and parent-child interactions but a negative influence of family size on family subjective well-being.